Storytelling and other activities for children in therapy - Slivinske, Johanna; Slivinske, Lee (Hoboken, New Jersey : John Wiley & Sons, 2011)
Storytelling can lead to successful therapeutic treatment with children confronting situations such as abuse or grief who may not be able to express their emotions directly. In this collection, the authors provide dozens of multicultural, modern stories that can help children and preteens gain mastery over their environment by controlling a story's ending--by talking about, writing about, or drawing their own endings. Mental health practitioners treating children and adolescents will benefit from the'cookbook' format providing quick access to activities and instructions --Provided by publisher.
How to Use This Book Chapter -- Principles and Processes of Therapeutic Storytelling -- The Strengths Approach to Storytelling with Children -- Developmental Issues of Children -- Illness and Disability -- School Issues -- Anger and Behavioral Issues -- Social Adjustment and Shyness -- Divorce and Parental Separation -- Domestic Violence -- Community Violence -- Trauma and Child Abuse -- Substance Abuse -- Cultural and Religious Issues -- Fun, Happiness and Strengths -- Accidents and Injuries -- Job Loss and Poverty -- Military Issues and International Violence -- Death -- General Activity Sheets for All Practice Areas.
Includes bibliographical references and indexes.
Keywords: Storytelling; Child psychotherapy; Narrative therapy; Psychotherapy -- methods; Adolescent; Child; Mental disorders -- Therapy; Narration